Flower vissitation patterns of Apis mellifera L. on the Andean blackberry - BOTERO-GARCÉS, NATALIA; MORALES-SOTO, GILBERTO (Revista Colombiana de Entomología, 1995)
The visitation patterns of Apis mellifera L. on the Andean blackberry flowers were studied in order to increase the beneficial effect and the use of the honey bee in the pollination of this crop. This research was carried out in Retiro (Antioquia) (bh-MB), in an Andean blackberry crop of 10 hectares. For its pollination, an apiary of 10 colonies were established, each colony with an approximate population of 30 thousand bees. A record was made of the time each bee took while visiting on the flower, and whether it collected nectar or pollen during the visit. The number of receptive flowers in 1 sq meter of blackberry plant was recorded, along with the number of bees visiting this area for 15 minutes, at different hours of the day, on different days. It was found that the honey bee visited the blackberry flower only to collect nectar, but in doing so still carries its pollen on her body from flower to flower. The mean visitation time per flower was 8 seconds; the number of receptive flowers per square meter was 22. The number of honey bees/m2/15 min varied greatly with the time of the day. The major activity recorded was between 10:00 a.m. and 4:30 p.m., with a peak from 1:00 to 2:00 p.m. The number of colonies required for the correct pollination of one hectare of the Andean blackberry is two, depending on the weather, topographic, and crop conditions, as well as the colonies themselves. It was concluded that the best schedule for the insecticide application was either in the morning before 9:00 a.m. or in the evening alter 6:00 p.m.